Modeling of borophene with density-functional tight-binding - Ukkola, Eerik (2020)
Borophene is a recently discovered two-dimensional allotrope of boron that hasshown unique electromechanical properties. In this study mechanical properties ofborophene are modeled with density-functional tight-binding (DFTB), which is amethod derived from density-functional theory (DFT). The goal of the study is toobtain direction-dependent bending stiffness of borophene by utilizing revised periodicboundary conditions (RPBC). The bending process can be simulated by applyingRPBC and creating copies of the initial borophene unit cell that are translated androtated. Difficulties arose during parametrization process of DFTB, since not allmechanical constants matched with DFT results. The DFTB results were exotic andindicated that one type of borophene lattice has negative bending stiffness. DFT calculations were conflicting and showed that DFTB calculations are likely to beinaccurate. Ultimately it was concluded that DFTB may not be a reliable methodfor modeling borophene.